A partnership transformed three decades of cooperation between the Asian Development Bank and the People Republic of China in support of reform and opening up. - Wihtol, Robert (Metro Manila, Philippines Asian Development Bank, 2018)
This publication explores three decades of cooperation between the Asian Development Bank and the People Republic of China in support of reform and opening up.
Keywords: Economic development -- China; Public-private sector cooperation -- China; Electronic books